The Safety and Efficacy of Laparoscopic Common Bile Duct Exploration Combined with Cholecystectomy for the Management of Cholecysto-choledocholithiasis: An Up-to-date Meta-analysis. Issue 2 (August 2018) - Pan, Long; Chen, Mingyu; Ji, Lin; Zheng, Longbo; Yan, Peijian; Fang, Jing; Zhang, Bin; Cai, Xiujun
Abstract : Objective: The aim of this study was to compare the efficacy and safety of the laparoscopic common bile duct exploration (LCBDE) and laparoscopic cholecystectomy (LC) with preoperative endoscopic sphincterotomy (pre-EST) and LC for concomitant gallstones and common bile duct (CBD) stones. Background: It remains controversial whether LCBDE+LC is better than pre-EST+LC for gallstones and CBD stones. Methods: A specific search of online databases was performed from January 2006 to October 2017. Relative outcomes of perioperative safety and postoperative efficacy were synthesized. Single-arm meta-analysis and cumulative meta-analysis were also conducted. Results: A total of 13 studies involving 1757 (872 vs 885) patients were included for analysis in our study. The CBD stones clearance rate [94.1% vs 90.1%; odds ratio (OR) 1.56, P = 0.012] was significantly higher in patients who underwent LCBDE+LC than pre-EST+LC, while perioperative complications (7.6% vs 12.0%; OR 0.67, P = 0.015), conversion to other procedure (4.1% vs 7.1%; OR 0.64, P = 0.025), retained stones rate (1.2% vs 7.9%; OR 0.34, P = 0.004), lithiasis recurrence rate (1.8% vs 5.6%, OR 0.32, P = 0.005), operative time [112.28 vs 132.03 minutes; weighted mean difference (WMD) −18.08, P = 0.002], length of hospital stay (4.94 vs 6.62 days; WMD −1.63, P = 0.023), and total charges [standardized mean difference (SMD) −2.76, P = 0.002] were significantly lower in LCBDE+LC. The mortality (0.6% vs 1.1%; OR 0.32, P = 0.117) was similar between the 2 groups. The cumulative meta-analyses indicated the effect sizes of CBD stones clearance rate, perioperative complications, and conversion to other procedure have already stabilized between 2 groups. Conclusion: The updated meta-analysis first confirms that LCBDE+LC is superior to pre-EST+LC both in perioperative safety and short- and long-term postoperative efficacy, which should be considered as optimal treatment choice for cholecysto-choledocholithiasis. Abstract : Supplemental Digital Content is available in the text